2021
DOI: 10.1002/1878-0261.12661
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA DANCR confers cytarabine resistance in acute myeloid leukemia by activating autophagy via the miR‐874‐3P/ATG16L1 axis

Abstract: Long noncoding RNA DANCR confers cytarabine resistance in acute myeloid leukemia by activating autophagy via the miR-874-3P/ATG16L1 axis AbstractAutophagy is an important mechanism involved in the regulation of acute myeloid leukemia (AML) chemoresistance. The long noncoding RNA (lncRNA) DANCR exhibits oncogenic activity in several types of human cancers, including AML, but it remains unclear whether it regulates autophagy and chemoresistance in AML. We report here that cytarabine (Ara-C) treatment elevates DA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 57 publications
3
26
0
Order By: Relevance
“… 26 , 27 In this case, suppressing autophagy sensitizes cancer cells to chemotherapy. 28 , 29 Furthermore, a growing volume of literature illustrates that suppression of autophagy can increase the sensitivity of CML cells to chemotherapy drugs. 4 , 30 , 31 Our study revealed that autophagy was related to chemoresistance in CML cells.…”
Section: Discussionmentioning
confidence: 99%
“… 26 , 27 In this case, suppressing autophagy sensitizes cancer cells to chemotherapy. 28 , 29 Furthermore, a growing volume of literature illustrates that suppression of autophagy can increase the sensitivity of CML cells to chemotherapy drugs. 4 , 30 , 31 Our study revealed that autophagy was related to chemoresistance in CML cells.…”
Section: Discussionmentioning
confidence: 99%
“…Most reports on lncRNAs are describing the sponge role through combining with miRNA in Arc‐C resistance 36–38 . However, other mechanisms of lncRNA involving in resistance have not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Most reports on lncRNAs are describing the sponge role through combining with miRNA in Arc-C resistance. [36][37][38] However, other mechanisms of lncRNA involving in resistance have not been reported. Our research showed that AC026150.8 has a scaffolding effect, which was partially verified and supplemented the result of Diogo M Ribeiro et al It can recruit splicing factors, and we speculate that AC026150.8 performs abnormal splicing on its target genes to make leukemia cells resistant to drugs.…”
Section: Ac0261508 Interacts With Alternative Splicing-related Proteinsmentioning
confidence: 99%
“…As shown in Table 1 , miR-874 is downregulated in at least 22 human malignancies, such as colorectal cancer (CRC) ( Huang et al, 2020a ; Yu et al, 2020 ; Que et al, 2017 ; Zhao and Dong, 2016 ; Han et al, 2016 ; Wang et al, 2021 ; Zhang et al, 2021c ), gastric cancer (GC) ( Huang et al, 2018 ; Sun et al, 2020 ; Yuan et al, 2020 ; Liu et al, 2017 ; Zhang et al, 2015 ; Jiang et al, 2014 ), hepatocellular carcinoma (HCC) ( Zhang et al, 2018b ; Jiang et al, 2017 ; Leong et al, 2017 ; Song et al, 2016 ), esophageal squamous cell carcinoma (ESCC) ( Yuan et al, 2018 ), pancreatic ductal adenocarcinoma (PDAC) ( Diao et al, 2018 ), non-small cell lung cancer (NSCLC) ( Bu et al, 2020 ; Yang et al, 2017 ; Ahmad et al, 2015 ; Kesanakurti et al, 2013 ; Wang et al, 2020b ), osteosarcoma (OS) ( Tang et al, 2018 ; Liu et al, 2020 ; Dong et al, 2016 ; Ghosh et al, 2017 ), epithelial ovarian cancer (EOC) ( Xia et al, 2018 ) cervical cancer (CC) ( Liao et al, 2018 ; Liu et al, 2021a ), retinoblastoma (RB) ( Zhang et al, 2018a ; Wang et al, 2020a ), prostate cancer (PCa) ( Pashaei et al, 2017 ) maxillary sinus squamous cell carcinoma (MSCC) ( Nohata et al, 2011 ), breast cancer (BC) ( Li et al, 2020 ; Zhang et al, 2017 ; Wang et al, 2014 ), triple-negative breast cancer (TNBC) ( Wu et al, 2020 ), rhabdomyosarcoma (RMS) ( Shang et al, 2019 ), papillary thyroid carcinoma (PTC) ( Ding et al, 2021 ), endometrial cancer ( Witek et al, 2021 ), cholangiocarcinoma ( Pan et al, 2021 ), glioma ( Li et al, 2021a ), myeloma (MM) ( Tian et al, 2021 ), head and neck squamous cell carcinoma (HNSCC) ( Nohata et al, 2013 ) and acute myeloid leukemia (AML) ( Zhang et al, 2021a ).…”
Section: The Aberrant Expression Of Mir-874 In Human Diseasesmentioning
confidence: 99%
“…Cancer cells use autophagy to provide energy and develop resistance to anti-cancer drugs; therefore, inhibiting autophagy may promote cancer cell death and help overcome drug resistance ( Levy et al, 2017 ). Autophagy involved in miR-874-3p is an important mechanism for regulating chemotherapy resistance in AML ( Zhang et al, 2021a ). In AML, the DANCR/miR-874-3p/ATG16L1 axis can promote autophagy, thereby enhancing the resistance of human AML cells to Ara-C ( Zhang et al, 2021a ).…”
Section: The Effect Of Mir-874 On Prognosis and Chemoresistancementioning
confidence: 99%